A Comparison of the Magmatic Evolution of Pacific Intraplate Volcanoes: Constraints on Melting in Mantle Plumes - Haase, Karsten M.; Beier, Christoph; Kemner, Fabian (Frontiers in Earth Science, 2019)
The interaction of deep mantle plumes with lithospheric plates is one fundamental concept of plate tectonics. Based on observations mainly made on the Hawaiian volcanoes the compositional evolution of hotspot volcanoes is believed to reflect the variation of partial melting and source composition as the plate moves across the different melting zones of the mantle plume. The model predicts the formation of several magmatic stages that differ in composition. In order to test this model, we compare published compositional and age data from the intraplate volcanoes of the Hawaii, Society, Marquesas and Samoa hotspots on the older part of the Pacific Plate. The compiled data indicate that most volcanoes display variations within and between several magmatic series, and in most cases the more evolved lavas are associated with the voluminous shield stage. The Hawaiian volcanoes show up to four different series ranging from tholeiites to nephelinites/melilitites, whereas the other hotspots mainly erupt two magmatic series consisting of transitional basalts and basanites. Submarine preshield stages at the Society and Marquesas hotspots resemble those observed at Hawaii. The large variation of primitive magmas in the Hawaiian plume as opposed to the other Pacific intraplate systems may reflect the higher temperatures, higher buoyancy flux and extreme chemical heterogeneity at Hawaii. The shield stage activity at all four hotspots lasts for 1 million years indicating similar widths of the melting zone, although the temperatures of the distinct mantle plumes vary considerably. The relatively depleted shield stage magmatism typically overlaps by ~200 kyrs with the formation of the more enriched postshield magmas indicating that the two melting and magma ascent systems exist contemporaneously.